Gender differences in crowd perception - Bai, Yang; Yamanashi Leib, Allison; Puri, Amrita; Whitney, David; Peng, Kaiping (Frontiers in Psychology, 2015)
In this study, we investigated whether the first impression of a crowd of faces—crowd perception—is influenced by social background and cognitive processing. Specifically, we explored whether males and females, two groups that are distinct biologically and socially, differ in their ability to extract ensemble characteristics from crowds of faces that were comprised of different identities. Participants were presented with crowds of similar faces and were instructed to scroll through a morphed continuum of faces until they found a face that was representative of the average identity of each crowd. Consistent with previous research, females were more precise in single face perception. Furthermore, the results showed that females were generally more accurate in estimating the average identity of a crowd. However, the correlation between single face discrimination and crowd averaging differed between males and females. Specifically, male subjects’ ensemble integration superiority slightly compensated for their poor single face perception; their performance on the crowd perception task was not as poor as would be expected from their single face discrimination ability. Overall, the results suggest that group perception is not an isolated or uniform cognitive mechanism, but rather one that interacts with biological and social processes.